Cost-utility analysis of second-line anti-diabetic therapy in patients with type 2 diabetes mellitus inadequately controlled on metformin. (2nd October 2020) - Chien, Ching-Lun; Chen, Yen-Chou; Malone, Daniel C.; Peng, Yueh-Lung; Ko, Yu
Abstract: Background: There are significant differences in costs and effectiveness among the second-line treatment options for type 2 diabetes (T2DM). We aimed to evaluate the cost-effectiveness of the second-line anti-diabetic therapy in T2DM patients inadequately controlled on metformin (MET) in Taiwan from the perspective of the National Health Insurance (NHI). Methods: The Cardiff T2DM model was used to predict the occurrence of mortality, diabetes-related complications, and drug adverse events. Five second-line treatments were selected for the analysis: sodium-glucose cotransporter 2 inhibitors (SGLT-2-i), glucagon-like peptide-1 receptor agonists (GLP-1-RA), dipeptidyl peptidase-4 inhibitor (DPP-4-i), sulfonylurea (SU), and insulin (INS). Treatment efficacy data were obtained from meta-analyses and randomized clinical trials, whereas cost data were derived from the NHI databases. Results: The analysis found that SU + MET (DPP-4-i as triple therapy) had the lowest cost, and SU + MET (SGLT-2-i as triple therapy) was associated with a mean incremental benefit of 0.47 quality-adjusted life years (QALYs) at an incremental cost of NT$2769, resulting in an incremental cost-effectiveness ratio (ICER) of NT$5840/QALY. Compared to their next less costly strategies, SGLT-2-i + MET (SU as triple therapy) and SGLT-2-i + MET (DPP-4-i as triple therapy) had ICER values of NT$63, 170/QALY and NT$64, 090/QALY, respectively. These results were fairly robust to extensive sensitivity analyses, but were relatively sensitive to baseline HbA1c, HbA1c threshold, and utilities. Conclusion: The addition of either SU or SGLT-2-i to MET was found to be cost-effective, using the 2019 forecast for GDP per capita of Taiwan (NT$770, 770) as the willingness to pay (WTP) threshold.